Efficacy Of Locally Delivered 1%(W/V) Natural Chitosan Gel In Nonsurgical.Treatment Of Chronic Periodontitis: A Split Mouth Study - Rani, Moka Leela; shaik, Abdul Riyaz; Jyotsna, Seemala; Suresh, Peddengatagari; Divya, Kathi; Anusha, Nimmakayala (Journal of Neonatal Surgery, 2025)
Introduction: Periodontal pocket elimination is one of the most important goals in the treatment of chronic periodontitis. Scaling, root planing and soft tissue curettage sometimes demonstrates limited success. Systemic antibiotics have been used in different forms of periodontal disease treatment. However, there may be problems associated with the use of systemic antibiotics such as the development of resistant bacteria, and potential side effects. These limitations can be avoided by application of the antimicrobials in local delivery systems directly into the periodontal pocket. Chitosan as a LDD agent has been investigated in the elimination of periodontal pocket. Objectives: The purpose of this study is to compare the efficacy of Chitosan gel as an adjunct to SRP in nonsurgical management of chronic periodontitis. Materials and methods:A randomised controlled clinical study was conducted to evaluate the clinical efficacy of chitosan gel in the treatment of PPD in Chronic periodontitis patient. A total of 20 subjects in the age group of 25-50 with chronic periodontitis are categorized into 2 treatment groups: Test group (SRP+ 1% Chitosan gel) and Control group (SRP) in a split mouth study. Various parameters such as PPD, BOP and GI were evaluated after 6 weeks. Results: Statistical significance is seen in the intra-group comparisons. No statistical difference was observed when intergroup comparison was done in PI and GI but there is significant difference in BOP and PPD. Conclusion: Chitosan's biocompatibility and inherent antibacterial properties may contribute to enhanced periodontal healing and tissue regeneration.